Gas adsorption and urea formation using magnetically induced environment - Yahya, N. (Springer Verlag, 2018)
Green urea synthesis is affected by magnetic field which alters the rate, yield, and output of the product. In this research, thermodynamic energy is replaced by magneto-dynamic energy to synthesize green urea using NiO nanoparticles. Comparative density functional theory (DFT) adsorption study of urea reactant gases (H2, N2, and CO2) over the NiO, CuO, and Fe2O3 nanocatalyst of few Ã dimension was investigated using adsorption locator and CASTEP modules, respectively. NiO nanoparticles were synthesized around 400Â Â°C by using simple slo-gel self-combustion technique. Nanoparticles size distribution, morphology and elemental analysis was investigated by TEM, FESEM, and EDX, respectively. Crystallinity and different phases of the nanoparticles were studied by XRD, Raman, and FTIR spectroscopies, respectively, while nanocatalyst magnetic properties were measured by using VSM. FESEM and TEM particle-size distribution analysis results depict the consistency in the range of (22â33Â nm) and (4â14Â nm), respectively. VSM results showed that saturation magnetization, retentivity, and coercivity values were 38.12Â emu/g, 3.298Â emu/g, and 83.12 G, respectively. By applying an external magnetic field of 2.4 T, the maximum concentration of 6666.86Â ppm of green urea was obtained for nanocatalyst mass of 0.322Â g under ambient conditions. Â© 2018, Springer Nature Singapore Pte Ltd.